A Study of Writing in the Secondary School. Final Report - Applebee, Arthur N.; National Council of Teachers of English, Urbana, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
The seven chapters of this final report provide a discussion of a study detailing the instructional situations within which students are learning to write. Data reported from the study include a national survey of teaching practices and many classroom observations in ninth and eleventh grade content area classrooms (English, mathematics, foreign language, science, social science, and business education). Following the first two chapters, which offer an overview of the study and its design, results from the various parts of the study are woven together in three chapters focusing on the major research topics: the types of writing students are asked to do, teachers' purposes in making these assignments, and the interaction of purposes with the writing instruction provided. The sixth chapter brings the major findings together, highlighting the results in outline form. The final chapter places the results in the context of the more general question of what is needed to improve writing instruction in the secondary school. In service of the same goal, an appendix provides a bibliography of materials that offer practical, classroom-oriented suggestions for incorporating writing into a variety of different subject areas. Other appendixes provide further details about results and instrumentation. (RL)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: NIE-G-79-0174.
ERIC Note: A number of pages may not reproduce due to small type.
Educational level discussed: High Schools.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Observation Techniques; Classroom Research; High Schools; Interdisciplinary Approach; National Surveys; Student Behavior; Teacher Attitudes; Teacher Behavior; Writing (Composition); Writing Research; Written Language; Writing across the Curriculum; Reports, Research